Control of planar magnetron sputtering system operating modes by additional anode magnetic field - Bizyukov, A.A.; Girka, O.I.; Sereda, K.N.; Sleptsov, V.V.; Chunadra, A.G. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
The control of planar magnetron sputtering system operating modes by additional anode magnetic field was investigated. It was shown that additional anode magnetic field substantially affects to planar magnetron-sputtering system (MSS) balancing and allows adjusting the electron fluxes intensity to the operating surface. It was experimentally shown that the magnetic field intensity increasing stabilizes the low-current discharge. The magnetic field intensity increasing prevents the discharge extinction by the ignition of semi-self-maintained magnetron-type discharge in transverse anode magnetic field.